An Analysis of the Student Responsibility Character Education Program Using the 5E Instructional Model by Bybee - Nur'akbar, Tomy; Subagyo, Ahmad (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This study aims to analyze character education programs, with a specific focus on fostering and enhancing students’ sense of responsibility through the 5E instructional model developed by Bybee. The 5E model comprising five phases: Engage, Explore, Explain, Elaborate, and Evaluate serves as a structured framework to support learning and behavioral development. At SMA Khalifa IMS, this model was intentionally integrated into several key programs and school activities such as the student council (OSIS), weekly flag ceremonies, live music sessions, Mukhoyyam Qur’an, Ramadan Camps, and Indonesian Independence Day celebrations. A qualitative research approach was employed, using program observation as the primary data collection method. Observations revealed that each stage of the 5E model plays a vital role in facilitating the internalization of responsibility among students. For instance, the Engage and Explore phases allowed students to reflect on real-life scenarios requiring accountability, while the Explain and Elaborate phases helped deepen their understanding through dialogue and practice. The Evaluate stage offered opportunities for feedback and self-assessment, reinforcing their growth. The findings suggest that the 5E model not only helps students grasp the theoretical aspects of responsibility but also promotes its consistent application in diverse school-life contexts. As a result, students develop a stronger sense of personal and collective responsibility. Implementing this model in character education enhances the learning experience and contributes to the cultivation of resilient, reflective, and responsible individuals.